Peningkatan Produktifitas Akademik Guru Melalui Pelatihan Pembuatan Media Berbasis Chatgpt Dan Join Research - Rino, Rino; Muskhir , Mukhlidi; Asriel, Armida S; Septrizola, Whyosi; Afdal, Zul (Manaruko: Jurnal Pengabdian Masyarakat, 2025)
Teachers as educational personnel are currently considered as a supporting component of education that is still weak in an effort to improve the quality of education. Four competencies that must be possessed by teachers are pedagogical competence, personality competence, social competence and professional competence, it turns out that pedagogical and professional competence are two competencies that are still low. This community service activity was carried out to help teachers strengthen the academic and professional competencies of teachers so as to increase academic productivity involving 23 participants. The problem-solving model offered is to conduct training in developing video learning media using the Camtasia application and training in preparing action research proposals using a collaboration of expository learning strategies (SPE) and problem-based learning strategies (SPBM). The implementation of this activity was carried out using the methods of lectures, questions and answers, guided exercises in person and online. After the guidance and training, there was an increase in teachers' pedagogic and professional competencies, especially in developing learning media and writing PTK proposals. Guru sebagai tenaga kependidikan saat ini dinilai sebagai komponen pendukung pendidikan yang masih lemah dalam upaya meningkatkan mutu Pendidikan. Empat kompetensi yang wajib dimiliki oleh guru yaitu kompetensi pedagogik, kompetensi kepribadian, kompetensi sosial dan kompetensi profesional, ternyata kompetensi kompetensi pedagogik dan profesional adalah dua kompetensi yang masih rendah. Kegiatan pengabdian masyarakat ini dilakukan untuk membantu guru-guru memperkuat kompetensi akademik dan professional guru sehingga meningkatkan produktifitas akademik yang melibatkan 23 orang peserta guru di SMAN1 Sungai tarab. Model pemecahan masalah yang ditawarkan adalah dengan melakukan pelatihan pengembangan media pembelajaran video dengan menggunakan aplikasi Camtasia dan pelatihan menyusun proposal action research dengan menggunakan kolaborasi strategi pembelajaran ekspositri (SPE) dan strategi pembelajaran berbasis masalah (SPBM). Pelaksana kegiatan ini dilakukan dengan metode ceramah, tanya jawab, latihan terbimbing secara langsung dan secara daring. Setelah dilakukan bimbingan dan pelatihan terlihat adanya peningkatan kompetensi pedagogic dan professional guru terutama dalam pengembangan media pembelajaran dan penulisan proposal PTK